Voluminous Omental Inflammatory Myofibroblastic Tumor in an Elderly Man: A Case Report and Literature Review - Pasquale Cianci; Antonio Ambrosi; Alberto Fersini; Nicola Tartaglia; Vincenzo Lizzi; Francesca Sanguedolce; Antonina Parafioriti; Vincenzo Neri (Case Reports in Surgery, 2015)
Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm of intermediate biologic potential, with uncertain etiology. This tumor occurs primarily in the lung, but the tumor may affect any organ system. A 75-year-old male was evaluated for voluminous palpable high abdominal mass with continuous and moderately abdominal pain, associated with abdominal distension for the last two months. Abdominal computed tomography showed a large (32×29×15 cm) heterogeneously enhanced mass with well-defined margins. At surgery, the mass originated from the greater omentum was completely excised. Histologically the tumor was a mesenchymal neoplasm in smooth muscle differentiation and was characterized by spindle-cell proliferation with lymphocytes, plasma cells, and rare eosinophils. Immunohistochemically, the tumor cells were positive for vimentin and smooth muscle actin and negative for anaplastic lymphoma kinase. Complete surgical resection of IMTs remains the mainstay of treatment associated with a low rate of recurrence. Final diagnosis should be based on histopathological and immunohistochemical findings. Appropriate awareness should be exercised by surgeons to abdominal IMTs in combination with constitutional symptoms, abnormal hematologic findings, and radiological definition, to avoid misdiagnosed.